A new dominantly inherited pure cerebellar ataxia, SCA 30. Issue 4 (7th November 2008) - Storey, E; Bahlo, M; Fahey, M; Sisson, O; Lueck, C J; Gardner, R J M
Abstract : Background: The spinocerebellar ataxias (SCAs) are clinically and genetically heterogeneous. Currently, 27 forms are known, with the causative gene identified in 16. Although the majority of dominant pedigrees worldwide have SCAs 1, 2, 3, 6 or 8, new SCAs continue to be delineated. We describe a new disorder: SCA 30. Methods: An Australian family of Anglo-Celtic ethnicity manifested a relatively pure, slowly evolving ataxia. Six affected and four unaffected members were personally examined in a standardised fashion. MRI and nerve conduction studies were performed in two. An autosomal genome-wide linkage study was undertaken, and an in silico analysis of potential candidate genes in the linkage region was performed. Results: The six affected members had a relatively pure, slowly evolving ataxia developing in mid to late life, with only minor pyramidal signs and no evidence of neuropathy. All had hypermetric saccades with normal vestibulo-ocular reflex gain. Only one displayed (slight) gaze-evoked nystagmus. MRI showed cerebellar atrophy with preservation of nodulus/uvula and brainstem. Linkage analysis excluded currently known SCAs and identified a logarithm (base 10) of odds score of 3.0 at chromosome 4q34.3–q35.1, distinct from all previously reported loci. In silico prioritisation identified the gene ODZ3 as the most likely contender. Conclusions: SCA 30 is a previously undescribed cause of (relatively) pure adult-onset autosomal dominant cerebellar ataxia. The responsible gene is yet to be determined, but ODZ3 is a plausible candidate.